Acrofacial vitiligo secondary to PI3KCA inhibitor, alpelisib: case report - Hinich, Maayan Geller; Hijab, Adham (Frontiers in Oncology, 2023)
Alpelisib plus fulvestrant is a valid second or advanced line of treatment for patients with metastatic hormone receptor (HR)-positive, HER2-negative breast cancer who harbor an activating PIK3CA mutation. The well-known side effects of alpelisib are hyperglycemia, rash, and diarrhea. Herein, we report a case of a woman who developed diffuse depigmented macules on the face, arms and legs, three months after initiating alpelisib. Both clinical and histopathological findings were consistent with new-onset vitiligo. To our knowledge, this is the first case described in literature which suggests a causal relationship between alpelisib and irreversible dermatological adverse effect.